2017
DOI: 10.1016/j.archoralbio.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Porphyromonas gingivalis and Tannerella forsythia to dentin and titanium with sandblasted and acid etched surface coated with serum and serum proteins – An in vitro study

Abstract: The present findings indicate that: a) single bacterial species (T. forsythia) can adhere more readily to titanium SLA than to dentin, b) low expression of T. forsythia protease inhibitor may influence the virulence of the species on titanium SLA surfaces in comparison with teeth, and c) surface properties (e.g. material and/or protein layers) do not appear to significantly influence multi-species adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…No data are currently available from the clinic for dental implants. However, we have recently shown in vitro that expression of gingipains was decreased when P. gingivalis attached to titanium surfaces compared with dentin surfaces . In this study, a decrease of gingipains expression over time was confirmed for bacterial suspension in cell culture medium.…”
Section: Discussionsupporting
confidence: 65%
“…No data are currently available from the clinic for dental implants. However, we have recently shown in vitro that expression of gingipains was decreased when P. gingivalis attached to titanium surfaces compared with dentin surfaces . In this study, a decrease of gingipains expression over time was confirmed for bacterial suspension in cell culture medium.…”
Section: Discussionsupporting
confidence: 65%
“…P. gingivalis cysteine proteases (gingipains) were always expressed both at implants and at teeth, which corroborates with results of our recent in vitro study using titanium and dentine disks. 32 The highest mRNA expression related to sod was found for kgp , followed by rgpA and rgpB . Level of Kgp was determined as being up to 10 nM in periodontium, 33 those of Arg-gingipains up to 1.5 μM.…”
Section: Discussionmentioning
confidence: 94%
“…Recently an in vitro study found that miropin expression was lower at titanium implants than at dentine disks. 32 However, the miropin expression by T. forsythia adhered either to the dentin or titanium surface exceeded up to 500-fold the expression of proteases (miropsin-1, miropsin-2, mirolase. 32 It is clear that more research is needed on T. forsythia , not only as the periodontal pathogen, but also a potentially pathogenic member of the peri-implant biofilm consortium.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have highlighted the indispensable role that implant surface roughness plays in bacterial adhesion [34]. Treatments, such as laser treatment, have gained popularity in dental therapy due to their benefits of low thermal damage; radiofrequency treatment (cold plasma) has also been shown to be capable of inhibiting microbial activity [42,43]. Bacterial colonization occurs during implantation or after osseous integration and interferes with the oral environment and material surface characteristics [44].…”
Section: Discussionmentioning
confidence: 99%